Programming high-speed and sprint running exposure in football: Beliefs and practices of more than 100 practitioners worldwide - Dello Iacono, A.; Beato, M.; Unnithan, V. B.; Shushan, T. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To gain knowledge on the beliefs and practices of football practitioners applying high-speed and sprint running exposure programming strategies.